Review of 1971/03/04 Concert at Town Hall, Birmingham. Concert of works by Handel, Dickinson and Elgar, given by the City of Birmingham Symphony Orchestra conducted by Maurice Handford, with Simon Preston as soloist. - Fairhurst, Peter (Contact: A Journal for Contemporary Music (1971-1990), 1971)